(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Salivary gland lesions comprise a heterogeneous group of inflammatory, benign, and malignant conditions that often present as glandular swellings. Fine Needle Aspiration Cytology (FNAC) is a minimally invasive, rapid, and cost-effective diagnostic technique widely used in the preoperative evaluation of salivary gland lesions. Histopathological examination remains the gold standard for definitive diagnosis. The present study was undertaken to evaluate the diagnostic accuracy of FNAC and correlate its findings with histopathological examination. Methodology: This prospective observational study was conducted in the Department of Pathology at Sree Mookambika Institute of Medical Sciences, Kulasekharam, from December 2024 to October 2025. Patients presenting with salivary gland lesions who underwent both FNAC and subsequent surgical excision were included in the study. FNAC was performed using a 22–25 gauge needle under aseptic precautions, and smears were stained with Hematoxylin and Eosin, May-Grünwald-Giemsa, and Papanicolaou stains. Histopathological examination of formalin-fixed surgical specimens was carried out and used as the reference standard. Cytological findings were compared with histopathological diagnoses to assess diagnostic performance. Results: FNAC demonstrated an overall diagnostic accuracy of 96% in differentiating benign and malignant salivary gland lesions. The sensitivity, specificity, positive predictive value, and negative predictive value were 77.0%, 98.9%, 90.9%, and 96.8%, respectively. Pleomorphic adenoma was the most common benign lesion, whereas mucoepidermoid carcinoma and adenoid cystic carcinoma were the predominant malignant tumors. Diagnostic discrepancies were mainly observed in cystic lesions and low-grade malignancies due to sampling limitations and overlapping cytological features. Conclusion: FNAC is a reliable and highly accurate diagnostic modality for the initial assessment of salivary gland lesions. Although certain diagnostic pitfalls exist, particularly in cystic and low-grade malignant tumors, FNAC remains an excellent preoperative investigation. Histopathological examination continues to be essential for definitive diagnosis and accurate tumor classification.